1997
DOI: 10.1016/s0169-5983(96)00042-1
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of dispersed turbulent multiphase flow

Abstract: Direct numerical simulations of homogeneous isotropic turbulence are used to investigate the effects of turbulence on the transport of particles in gas flows or bubbles in liquid flows. The inertia associated with the bubbles or the particles leads to locally strong concentrations of these in regions of instantaneously strong vorticity for bubbles or strain-rate for particles. This alters the average settling rates and other processes. If the mass-loading of the dispersed phase is significant a random "turbule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(74 citation statements)
references
References 14 publications
3
70
0
1
Order By: Relevance
“…As additional examples, Maxey et al (1997) and Saw et al (2008) reported numerical and experimental evidence, respectively, of spatial clustering of dense particles in high-Re homogenous, isotropic turbulence. The dissipation-scale clustering was found to become stronger for increasing values of the Stokes number.…”
Section: Introductionmentioning
confidence: 98%
“…As additional examples, Maxey et al (1997) and Saw et al (2008) reported numerical and experimental evidence, respectively, of spatial clustering of dense particles in high-Re homogenous, isotropic turbulence. The dissipation-scale clustering was found to become stronger for increasing values of the Stokes number.…”
Section: Introductionmentioning
confidence: 98%
“…A fully resolved method which is based on matching explicit Stokes flow representations of flow near particles with computations on a grid has been proposed by Ory, Oguz and Prosperetti [2000]. The problem of particulates in turbulent flows has been considered by a few authors: Crowe, Chung, Troutt [1996], McLaughlin [1994], Maxey, Patel, Chang, Wang [1997]; these approaches use point particle approximations because fully resolved computations in turbulent flow are not presently possible. Numerical approaches to particulate flow based on the discrete Lattice Boltzmann equation have been presented by Ladd [1994Ladd [ , 1996Ladd [ , 1997 Aidun [1996], Aidun, Lu and Ding [1998] and Qi [1997Qi [ , 1999.…”
Section: Introductionmentioning
confidence: 99%
“…The microbubble limit was used in the PPDNS study of microbubbles in Wang and Maxey (1993b) and Maxey et al (1997). For the fully buoyant particle limit, the equation of motion becomes solvable to yield V À U ¼ ðV À UÞj t¼0 expðÀt=s p Þ with s p ¼ a 2 =ð3mÞ so the particle quickly approaches the fluid velocity.…”
Section: Lagrangian Tracking Of Particlesmentioning
confidence: 99%